A LAB-ON-A-CHIP DEVICE WITH INTEGRATED GOLD NANOSENSORS FOR THE ULTRASENSITIVE ELECTROCHEMICAL DETECTION OF DENGUE VIRUS BIOMARKERS - Andri Setiawan; Luis Santos; Josefa Flores (Yayasan Adra Karima Hubbi, 2025)
Dengue fever is a significant global health threat, where rapid and accurate diagnosis is crucial for timely clinical intervention and outbreak management. Conventional diagnostic methods are often centralized, time-consuming, and require sophisticated equipment, limiting their utility in point-of-care (POC) settings. This study reports the development and validation of a novel lab-on-a-chip (LoC) device integrating gold nanosensors for the ultrasensitive electrochemical detection of the Dengue virus non-structural protein 1 (NS1). The microfluidic device was fabricated using soft lithography, and the gold electrode surfaces were functionalized with specific anti-NS1 monoclonal antibodies. Detection was performed using differential pulse voltammetry (DPV), measuring the change in current response upon immunocomplex formation. The developed immunosensor exhibited a wide linear dynamic range and an exceptionally low limit of detection (LoD) of 1.5 pg/mL for the NS1 antigen. Furthermore, the device demonstrated high selectivity against other interfering proteins. Our findings successfully establish a robust, miniaturized LoC platform for the rapid and highly sensitive detection of dengue biomarkers. This device holds significant potential as a powerful POC diagnostic tool for the early detection of dengue fever, particularly in resource-limited environments.